2009
DOI: 10.1111/j.1600-0404.1994.tb02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural evolution of snoring: a 5-year follow-up study

Abstract: Introduction– The natural evolution of snoring was studied in a middle‐aged population in Finland. Material and methods– A questionnaire was mailed to a stratified random sample of 1600 people aged 36–50 years in 1985 with a response rate of 75.2%; 53% of them completed also the 5‐year‐follow‐up questionnaire. Clinical examinations (N = 36) and whole‐night polygraphic recordings (N = 22) were made to habitual (every or almost every night) snorers and daily sleepy persons. Results– A total of 626 persons comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…The prevalence of snoring was found to be 127 patients including 100 males (78.7%), their ages were 42.6 ± 14.61 and 27 females (21.3%), and their ages were 53.2 ± 18.25 age ranged between 15 and ˃75 years ( Figure 1). Comparing with previous studies done for snoring; men and women showed an increase of snoring in mid-life [27]- [29]. In other study of patients between 30 and 60 years of age, the highest prevalence were found among men between 50 and 60 years.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The prevalence of snoring was found to be 127 patients including 100 males (78.7%), their ages were 42.6 ± 14.61 and 27 females (21.3%), and their ages were 53.2 ± 18.25 age ranged between 15 and ˃75 years ( Figure 1). Comparing with previous studies done for snoring; men and women showed an increase of snoring in mid-life [27]- [29]. In other study of patients between 30 and 60 years of age, the highest prevalence were found among men between 50 and 60 years.…”
Section: Discussionmentioning
confidence: 72%
“…Large population based studies have shown an increasing trend in prevalence of snoring up to the age group of 60 -69 years in Finland [31] and up to 60 -70 years in Spain [32]. Other studies have reported higher prevalence among middle-aged populations: 44% in men and 28% in women in the USA and 28% -44% and 6% -19% in Finland, respectively [27] [30] [31]. Men have 2-to 3-fold greater risk of snoring than women, but mechanisms underlying this difference are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Martakinen ve ark. 20 basit horlayanların %23'ünün hayatlarında en az bir kez direksiyon başında uyuduğunu ve bu olgularda kaza yapma riskinin %4,5 olduğunu bildirmişlerdir [15]. OUAS'lu hastalarda kaza yapma riski ile hastalığın ağırlığını gösteren apne-hipopne indeksi arasında doğrusal ilişki olduğu bildirilmiştir.…”
Section: Discussionunclassified
“…Heavy habitual (every night) snoring (i.e., partial upper-airway obstruction), even without apneas, may influence pulmonary arterial pressure, and it is associated with daytime sleepiness, arterial hypertension, insulin resistance, metabolic syndrome and other health consequences (Lugaresi et al, 1975(Lugaresi et al, , 1983bPartinen et al, 1983bPartinen et al, , 1998Koskenvuo et al, 1985b;Rauscher et al, 1992;Tiihonen et al, 1993;Martikainen et al, 1994;Grunstein et al, 1995;Grunstein, 1996;Young et al, 1996Young et al, , 1997Fuyuno et al, 1999;Hu et al, 1999Hu et al, , 2000Bixler et al, 2000;Franklin et al, 2000;Lavie et al, 2000;Peppard et al, 2000;Leineweber et al, 2003).…”
Section: Habitual Snoringmentioning
confidence: 99%